Geochemistry of vein calcites hosted in the troodos pillow lavas and their implications for the timing and physicochemical environment of fracturing, fluid circulation, and vein mineral growth - Quandt, Dennis; Micheuz, P.; Kurz, W.; Kluge, Tobias; Boch, R.; Hippler, D.; Krenn, K.; Hauzenberger, C. A. (Geochemistry, geophysics, geosystems, 2019)
Calcite veins hosted in pillow lavas of the Late Cretaceous Troodos suprasubduction zone ophiolite provide insights into the timing and physicochemical environment of postmagmatic fracturing and fluid circulation through oceanic crust. This study presents rare earth element and yttrium (REE+Y) concentrations, δ13C, δ18O, 87Sr/86Sr, and clumped isotopic (Δ47) compositions of vein calcites in order to investigate their fluid sources, formation temperatures, and precipitation ages. These geochemical data are combined with microtextural analyses. Intersections of 87Sr/86Sr ratios of vein calcites with the Sr isotope seawater curve suggest two distinct calcite veining phases. Major calcite veining within an interval of 10 Myr after crust formation is characterized by microtextures that point to extensional fracturing related to crack and sealing, host rock brecciation, and advective fluid flow. These vein calcites show REE+Y characteristics, 87Sr/86Sr ratios, and clumped isotopic compositions indicative of precipitation from seawater at <50 °C. Extended fluid residence times intensified fluid-rock interactions and lowered Y/Ho ratios of some blocky vein calcites, whereas crack and sealing resulted in pristine seawater signatures. Low 87Sr/86Sr ratios of localized high-temperature blocky vein calcites point to the involvement of hydrothermal fluids. These calcites show Mn-controlled oscillatory growth zonations that probably developed in a closed system out of equilibrium. Later calcite veining (<75 Ma) may have coincided with rotation and/or uplift of the Troodos ophiolite. Microtextures of these vein calcites indicate fluid diffusion and fracture-independent crystallization pressure-driven veining. Their variably modified seawater signatures resulted from diffusion-related fluid interaction with hydrothermal sediments.